PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DALAM MENINGKATKAN PRODUKTIVITAS KERJA PADA PT NGK CERAMICS INDONESIA - Wahyu Murti dan Siska Apandi (Jurnal Manajemen FE-UB, 2016)
By taking a sample of 50 contract employees and remain in PT.NGK Ceramics Indonesia, To solve the problems with analyzing and testing the relationship and influence between the independent variables on the dependent variable used models kausalistik through path analysis (Path Analisys) with SPSS 20. The results showed that the analysis, (1) Compensation direct significant positive effect on employee performance acceptable, analysis (2) work environment direct significant positive effect on employee performance acceptable, analysis (3) compensation direct significant positive effect on work productivity accepted, analysis (4) work environment direct significant positive effect on work productivity accepted, analysis (5) employee performance direct significant positive effect on work productivity accepted, analysis (6) the magnitude of positive and significant influence indirectly Compensation for productivity through employee performance acceptable, analysis (7) the magnitude of positive and significant impact indirectly on the productivity of the work environment through employee performance acceptable. Keywords: Compensation, Work Environment, Performance And Productivity